How Firm Characteristics Affect the Dividend Policy of Listed Banking Companies on The Indonesian Stock Exchange in 2019-2021 - Saitri, Putu Wenny; Mendra, Ni Putu Yuria; Pramesti, I Gusti Ayu Asri; Renaldo, Nicholas (First Ciera Publisher, 2023)
This study aims in this study to determine the effect of profitability, managerial ownership, liquidity, company size, and debt policy on dividend policy. The population in this study is the population in this study, namely all banking companies registered on the Indonesia Stock Exchange (IDX) in 2019-2021, namely 46 banking companies with a total sample of 41 companies determined by the purposive sampling method. The data analysis technique used in this study is multiple linear regression, coefficient of determination, t-test, and F-test. Based on the research results, it can be seen that Profitability has a positive effect on dividend policy in banking companies listed on the Indonesia Stock Exchange in 2019-2021. Managerial Ownership and Debt Policy have a negative effect on dividend policy in banking companies listed on the Indonesia Stock Exchange in 2019-2021. Meanwhile, Liquidity and Company Size Have No Effect on Dividend Policy in banking companies listed on the Indonesia Stock Exchange for 2019-2021. The adjusted R square value in this study is still not strong, namely 0.442 or 44.2% so further research is expected to be able to increase the adjusted R square value by examining and adding other variables which in theory have an influence on dividend policy. The advice that can be given by researchers is that in the future the company is expected to be able to increase its profitability so that later the company is able to distribute high dividends to its investors.